2021
DOI: 10.1016/j.ebiom.2021.103243
|View full text |Cite
|
Sign up to set email alerts
|

Increased apolipoprotein-B:A1 ratio predicts cardiometabolic risk in patients with juvenile onset SLE

Abstract: Background Cardiovascular disease is a leading cause of mortality in patients with juvenile-onset systemic lupus erythematosus (JSLE). Traditional factors for cardiovascular risk (CVR) prediction are less robust in younger patients. More reliable CVR biomarkers are needed for JSLE patient stratification and to identify therapeutic approaches to reduce cardiovascular morbidity and mortality in JSLE. Methods Serum metabolomic analysis (including >200 lipoprotein measures)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 67 publications
(53 reference statements)
0
28
0
Order By: Relevance
“…In that study, ApoB and ApoA1 were stronger predictors of abnormal vascular changes than conventional cholesterol measurements (LDL-C and HDL-C), which suggests that the carriers (apolipoproteins) might play a more central role than the actual lipid content transported in these lipoprotein particles. These findings are further supported by the Pathobiological Determinants of Atherosclerosis in Youth study which found apolipoproteins associated with post-mortem arterial lesions, [19] and the Bogalusa Heart Study, which showed that high ApoB/ApoA1 ratio in children was associated with incidence of parental myocardial infarction, [20] and a recent publication identifying ApoB/ApoA ratio as a predictor of cardiovascular risk in adolescent SLE patients [21] . A recent study also showed that increased ApoB/ApoA1 ratio predicts cardiometabolic risk in patients with juvenile onset systemic lupus erythematosus [21] .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In that study, ApoB and ApoA1 were stronger predictors of abnormal vascular changes than conventional cholesterol measurements (LDL-C and HDL-C), which suggests that the carriers (apolipoproteins) might play a more central role than the actual lipid content transported in these lipoprotein particles. These findings are further supported by the Pathobiological Determinants of Atherosclerosis in Youth study which found apolipoproteins associated with post-mortem arterial lesions, [19] and the Bogalusa Heart Study, which showed that high ApoB/ApoA1 ratio in children was associated with incidence of parental myocardial infarction, [20] and a recent publication identifying ApoB/ApoA ratio as a predictor of cardiovascular risk in adolescent SLE patients [21] . A recent study also showed that increased ApoB/ApoA1 ratio predicts cardiometabolic risk in patients with juvenile onset systemic lupus erythematosus [21] .…”
Section: Discussionmentioning
confidence: 67%
“…These findings are further supported by the Pathobiological Determinants of Atherosclerosis in Youth study which found apolipoproteins associated with post-mortem arterial lesions, [19] and the Bogalusa Heart Study, which showed that high ApoB/ApoA1 ratio in children was associated with incidence of parental myocardial infarction, [20] and a recent publication identifying ApoB/ApoA ratio as a predictor of cardiovascular risk in adolescent SLE patients [21] . A recent study also showed that increased ApoB/ApoA1 ratio predicts cardiometabolic risk in patients with juvenile onset systemic lupus erythematosus [21] .…”
Section: Discussionmentioning
confidence: 67%
“…Evidence suggests that lipoprotein biomarkers could be used predict atherosclerotic risk in adults with SLE [ 146 , 147 ]. A study using in-depth metabolomics by Robinson et al identified that the ApoB:ApoA1 ratio was a strong biomarker of CVD in JSLE, independent of clinical disease measures and body mass index (BMI) [ 118 ]. This finding has been validated in 2 separate cohorts using ultrasound evidence for the presence of subclinical atherosclerotic plaque in adult SLE patients [ 146 ].…”
Section: Renal Biomarkersmentioning
confidence: 99%
“…In this issue of EBioMedicine, Robinson and co-workers identified a novel risk marker, apolipoprotein B (apoB)-to-apoA1 ratio, from an investigation integrating metabolomics, transcriptome, immune profiles, and clinical data of patients with JSLE. They verified its usefulness by conducting longterm observational clinical cohort studies and comparing clinical information between adult patients with SLE and mouse atherosclerotic models [4].ApoB and apoA1 are major apolipoproteins involved in lipid transport and the pathogenic processes and complications of atherosclerosis. These are the major protein components in very-low-, intermediate-, and low-density lipoproteins, with one protein per particle, and in high-density lipoprotein particles, respectively [5].…”
mentioning
confidence: 94%
“…In this issue of EBioMedicine, Robinson and co-workers identified a novel risk marker, apolipoprotein B (apoB)-to-apoA1 ratio, from an investigation integrating metabolomics, transcriptome, immune profiles, and clinical data of patients with JSLE. They verified its usefulness by conducting longterm observational clinical cohort studies and comparing clinical information between adult patients with SLE and mouse atherosclerotic models [4].…”
mentioning
confidence: 95%